Effect of Atmospheric Packaging Method on Quality of Ready-to-eat Cooked Rice from IR 64 Rice (Oryza sativa L. indica) - Anggita Nugrahanto; Supriyadi Supriyadi; Yudi Pranoto (Indonesian Association of Food Technologists, 2018)
Rice is considered as staple food that consumed in the form of steamed rice. Due to the emergency condition, like volcano eruption or flood, the availability and accessibility might be a serious problem. Therefore, a ready-to-eat rice is necessary. It would need a design processing condition to produce practical cooked rice in more economically packaging with different method.Normal packaging and vacuum packaging of cooked rice followed by steaming for 60 minutes was conducted in this study. Two different storage temperatures include cold and room storage in day 0, 1, 4, and 7 was used to evaluate. The result showed that vacuum packaging gave better reduction in microbial parameter. However, panelist gave same preference in both normal and vacuum packaged cooked rice. Overall, cold stored-packaged cooked rice gave better quality than room stored-packaged cooked rice, especially in microbial parameter. Thus, combination of vacuum packaging and cold storing could be an alternative way to produce cooked rice which can be consumed in difficult condition.